p PENGARUH NON-PERFORMING LOAN DAN SUKU BUNGA BANK INDONESIA TERHADAP LABA BERSIH PT. BANK MEGA : Indonesia - Lukman Hakim (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study was conducted to determine the effect of non-performing loans and the effect of bank interest rates on the performance of a bank with net income in the range of 2013 to 2019. This study uses SPSS and interviews as primary instruments in obtaining and analyzing data, the results of this study is that NPL has no significant effect on Bank Mega's net profit, and Bank Indonesia's interest rate also does not have a significant effect on Bank Mega's net profit, then it is also found that NPL and Bank Indonesia's Interest Rate simultaneously contribute 9.3% to profit Bank Mega's net and the remaining 90.7% is influenced by other unknown factors. Keywords: Non Performing Loan, Bank Indonesia interest rate, net profit